Otonomi Desa dan Pergeseran Kekuasaan Elit Lokal - Syahrir Karim (ILMU POLITIK UNIVERSITAS ISLAM NEGERI (UIN) ALAUDDIN MAKASSAR, 2022)
The reform era has changed the paradigm of the state in viewing villages, especially villages based on customs. This can be seen in looking at the relationship between the village government and custom, as well as the relationship between the village government and the community, especially in customary laws and the government in this case the state. Then there will be a dialogue, compromise or negotiation is built and often even causes resistance by one part. This situation will forms a new social construct in the form of space struggles, debates and spaces to search for individual identities. Finally, the Ammatoa indigenous community as a local community (indigenous peoples) seems to be in a subordinated position by the state. Therefore, as the only way, they always look for spaces for negotiation or even compromise in dealing with the state in order to maintain an existence.